7th International conference NBP-2021 “Nanobiophysics: fundamental and applied aspects” - KarachevtsevV. А.; Kosevich, M. V.; Dovbeshko, G. I. (Biophysical Bulletin, 2022)
7th International conference “NANOBIOPHYSICS: Fundamental and Applied Aspects” (NBP-2021) took place on October 4-8, 2021 at B. Verkin Institute for Low Temperature Physics and Engineering of the National Academy of Sciences of Ukraine (Kharkiv, Ukraine). Previous six conferences, starting from 2009, were organized due to joint efforts of B. Verkin Institute for Low Temperature Physics and Engineering of the NAS of Ukraine and Institute of Physics of the NAS of Ukraine on biennial basis in Kharkiv and Kyiv alternatively. Among 80 registered participants from 16 countries about 40 scientists have presented their lectures and posters offline and other participants were joining the sessions online. 16 keynote lectures and 18 oral presentations were made and 51 posters were discussed offline and online. The goal of the conference was achieved: urgent problems, advances and perspectives of the topical scientific direction of nanobiophysics which embraces achievements of modern molecular biophysics and nanotechnology were discussed. The subjects of physical aspects of biomolecular nanosystems, properties of biomolecules on nanoparticles and nanostructured surfaces, nanobiohybrids formation by 1-D or 2-D nanomaterials with bioobjects, theoretical calculations and computer modeling of nanobiosystems, and applied aspects of nanobiophysics were highlighted at the related sessions. Several additional accompanying events were organized in the framework of the conference, including a Round Table “How biophysics and nanosciences meet modern challenges: the case of COVID-19”, a special session of the Ukrainian Biophysical Society, and SPIE (The International Society of Optics and Photonics) and OSA (The Optical Society) Workshop “Career development opportunities for young scientist and students”. Book of abstract based on NBP-2021 materials was published.